General pathologist-helper: The new medical app about general pathology - Iván Fernandez-Vega (Elsevier, 2015)
Introduction: Smartphone applications (apps) have become increasingly prevalent in medicine. Due to most pathologists, pathology trainees, technicians, and medical students use smartphones; apps can be a different way for general pathology education. "General pathologist-helper (GP-HELPER)" is a novel app developed as a reference tool in general pathology and especially for general pathologists, developed for Android and iOS platforms. Materials and Methods: "GP-HELPER," was created using Mobincube website platform. This tool also integrates "FORUM GP-HELPER," an external website created using Miarroba website (http://forum-gp-helper.mboards.com) and "COMMUNITY GP-HELPER" a multichannel chat created using Chatango website platform. Results: The application was released in July 2015, and it is been periodically updated since then. The app has permanent information (offline data) about different pathology protocols (TNM latest edition, protocols regarding management of tumors of unknown primary origin, and flowcharts for some of the most difficult tumors to diagnose) and a database with more than 5000 immunohistochemistry results from different tumors. Online data have links to more than 1100 reference pathology video lectures, 250 antibodies information, more than 70 pathology association websites, 46 pathology providers, and 78 outstanding pathology journal websites. Besides this information, the app has two interactive places such as "FORUM GP-HELPER" and "COMMUNITY GP-HELPER" that let users to stay in touch everywhere and every time. Expert consult section is also available. Conclusions: "GP-HELPER" pretends to integrate offline and online data about pathology with two interactive external places in order to represent a reference tool for general pathologists and associate members.